The effect of a tuberculosis chest X-ray image reference set on non-expert reader performance - Waitt, Catriona J. (Springer Berlin Heidelberg, 2013)
OBJECTIVES: In low-resource settings, limitations in diagnostic accuracy of chest X-rays (CXR) for pulmonary tuberculosis (PTB) relate partly to non-expert interpretation. We piloted a TB CXR Image Reference Set (TIRS) to improve non-expert performance in an operational setting in Malawi. METHODS: Nineteen doctors and clinical officers read 60 CXR of patients with suspected PTB, at baseline and using TIRS. Two officers also used the CXR Reading and Recording System (CRRS). Correct treatment decisions were assessed against a “gold standard” of mycobacterial culture and expert performance. RESULTS: TIRS significantly increased overall non-expert sensitivity from 67.6 (SD 14.9) to 75.5 (SD 11.1, P = 0.013), approaching expert values of 84.2 (SD 5.2). Among doctors, correct decisions increased from 60.7 % (SD 7.9) to 67.1 % (SD 8.0, P = 0.054). Clinical officers increased in sensitivity from 68.0 % (SD 15) to 77.4 % (SD 10.7, P = 0.056), but decreased in specificity from 55.0 % (SD 23.9) to 40.8 % (SD 10.4, P = 0.049). Two officers made correct treatment decisions with TIRS in 62.7 %. CRRS training increased this to 67.8 %. CONCLUSION: Use of a CXR image reference set increased correct decisions by doctors to treat PTB. This tool may provide a low-cost intervention improving non-expert performance, translating into improved clinical care. Further evaluation is warranted. KEY POINTS: • Tuberculosis treatment decisions are influenced by CXR findings, despite improved laboratory diagnostics. • In low-resource settings, CXR interpretation is performed largely by non-experts. • We piloted the effect of a simple reference training set of CXRs. • Use of the reference set increased the number of correct treatment decisions. This effect was more marked for doctors than clinical officers. • Further evaluation of this simple training tool is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00330-013-2840-z) contains supplementary material, which is available to authorized users.